NILAI-NILAI PENDIDIKAN ISLAM DI PESANTREN DALAM NOVEL CAHAYA CINTA PESANTREN - Khadijah Khadijah (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2014)
Values are very influential on a person’s behavior. Many people e still assume that the establishment of a pesantren is only for naughty childreen, even though the pesantren was established to shape the spiritual mentality of students in all fields. This research was conducted on some of the uniqueness found in the novel Cahaya Cinta Pesantren by Ira Madan, including the novel which is written in light and easy to understand language, providing inspiration and motivation to the readers. In this novel, there are many messages of Islamic education in Islamic boarding schools. Based on this uniqueness, researchers are interested in making the novel Cahaya Cinta Pesantren by Ira Madan as the object of researchers with the title “The Values of Islamic Education in Islamic Boarding Schools in the Novel Cahaya Cinta Pesantren by Ira Madan”. This type of researcher is a library research researcher with a qualitative approach. Data analysis techniques using content analysis or content analysis. That is drawing conclusions are obtained: first, the themes contained in the novel Cahaya Cinta Pesantren by Ira Madan is about Islamic teachings in Islamic boarding schools. Second, the values of Islamic education in pesantren in the novel Cahaya Cinta Pesantren by Ira Madan are: (a) The value of the soul of sincerity when undergoing trials, teaching, and learning; (b) the value of the spirit of simplicity in appearance and dress; (c) the value of the spirit of independence in all things without expecting help from others; (d) the value of the spirit of ukhuwah Islamiyah by always establishing a close relationship of brotherhood by not dicriminating in all respects; (e) the value of freedom in determining the future, thinking and having opinions.